Intellectual review of “Shahar-e-Madina Aisa Hai” by Hafiz Muhammad Hussain Hafiz: ’’ شہر مدینہ ایسا ہے‘‘از حافظ محمدحسین حافظؔ کا فکری جائزہ - Iqbal, Saima; Yasmeen, Rubina; Afzal, Aneesa (Al Khadim Research Journal of Islamic Culture and Civilization, 2021)
Hafiz Muhammad Hussain Hafiz(1993-2010) is from Faisalabad,Pakistan. He is very successful Punjabi poet.At the public level ,his Natya Kalam is still read with great relish.He used to write in Urdu from time to time. God-given ability and extensive personal study, as well as the lifelong companionship of scholars, his thoughts and writings produce many virtues.Naat is fact a statement of the attributes of the Holy Prophet (PBUH). The Holy prophet is beloved of Allah and His creatures. He is the cause of the creation of the universe and the mercy of the worlds. His example of beauty is the best example for all believers.Hafiz Muhammad Hussain, s book “Shahar-e-Madina Asia Hai” in his naat has mentioned the caste, attributes and virtues of the Holy Prophet in a beautiful way.If his Naats are carefully studied,then the first of all his theory of Naat comes to the fore.His two Naatiya books “ Sarkar ki Gali Main” and “ Shahar –e- Madina Aisa Hai” are in Urdu. In this article an intellectual review of his Natya book “ Shahar Madina Aisa Hai” has presented.